1991
DOI: 10.1002/j.1460-2075.1991.tb07746.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationship study of human interleukin-3: role of the C-terminal region for biological activity.

Abstract: A structure‐activity relationship study of human interleukin‐3 (huIL‐3) was performed by functional analysis of huIL‐3 deletion and substitution variants combined with epitope mapping of huIL‐3 specific neutralizing monoclonal antibodies (mAb). Analysis of the huIL‐3 variants was accomplished by defining their capacity to compete with wild‐type huIL‐3 for binding to the huIL‐3 receptor and to induce the proliferation of the huIL‐3 dependent cell line M‐O7. HuIL‐3 variants with either 14 amino acids (aa) delete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 30 publications
(13 reference statements)
2
29
1
Order By: Relevance
“…Although the previous authors (7,8) did not demonstrate strong modification of the three-dimensional structure after the mutation, our in silico studies indicated that the conformation of the mutein (Fig. 4B) was significantly different from that of the non-mutated protein (Fig.…”
Section: In Silico Docking Of the Ligands Of Il-3 In The Il-3contrasting
confidence: 73%
See 3 more Smart Citations
“…Although the previous authors (7,8) did not demonstrate strong modification of the three-dimensional structure after the mutation, our in silico studies indicated that the conformation of the mutein (Fig. 4B) was significantly different from that of the non-mutated protein (Fig.…”
Section: In Silico Docking Of the Ligands Of Il-3 In The Il-3contrasting
confidence: 73%
“…Indeed, site-directed mutagenesis (7, 8, 23, 27, 40 -43) of human IL-3 defined essential amino acids for binding to the IL-6R␣ and -3R␤ as residues Ser-17, Asn-18, Asp-21, Arg-22, Thr-25, Ser-42, Glu-43, Gln-45, Asp-46, Met-49, Arg-94, Pro-96, Arg-108, Lys-110, Leu-111, Phe-113, Lys-116, and Glu-119. Deletion of the first 14 amino acids (40) did not modify the receptor binding of IL-3, a property lost when the first 18 amino acids were deleted (8). No biological activity was found after deletion of the 22 C-terminal amino acids (8).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The fragment was cloned as an NdeI -SnaI fragment into an expression vector (pIP998) modified from pL-RCV (Lokker et al, 1991). In this plasmid, pNB2, lipAL transcription was directed by the bacteriophage X pL promoter controlled by the temperature-sensitive cI857 repressor in the chromosome of W31 10 (Lokker et al, 1991) Oligonucleotide 3, GCCCATATGGGAATCAACCTCACCCCG; Oligonucleotide 4, GGCGGCGTCCATGGCCCC.…”
Section: Purification Of Proteinsmentioning
confidence: 99%